The Role of Various Powders during the Hydration Process of Cement-Based Materials - Shuhua Liu; Hongling Wang; Jianpeng Wei (Advances in Materials Science and Engineering)
The role of various powders including glass powder (GP), limestone powder (LP), and steel slag powder (SSP) during the hydration process of cement-based materials was investigated by using X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), scanning electron microscopy (SEM), and strength tests. GP has adverse impact on early strength, but the pozzolanic reaction at later stage enhances the strength development greatly. LP can significantly improve early strength. SSP has a good contribution to the early and later strength of the paste when its content is less than 15%. GP has little effect on the kind of hydration products but relatively large effects on the quantity. Calcium hydroxide (CH) content of GP paste decreases over curing age gradually, which is different from pure cement paste because its pozzolanic activity consumes more CH than that generated from the cement hydration. SSP and LP mainly play a role of filling effect at early stage. Nucleating effect of LP also promotes the early hydration of cement. The hydration of LP occurs at later stage and forms the calcium carboaluminate hydrates. The hydration of SSP is relatively slow, which generates CH at later stage and is effective in the strength development.